Online business-to-business communication and online relationship: The mediator role of trust - Vilas Boas, A.F.; Guerreiro, J.; Marques, C. (Proceedings of the 48th EMAC Conference, 2019)
The main purpose of this study is to examine the influence of online personalised content and interactive content communication on online relationship through trust as an affective mediator in a Business-to-Business (B2B) context. A quantitative research approach was conducted using structural equation modelling and a sample of B2B reseller market of information technology in Portugal. Results indicate that online communication influences positively online relationship through trust. Interactive content has a strong influence on trust, whereas the personalised content revealed a weak relationship with trust and, indirectly, with online relationship. Trust has an important role in the relationship as it is a full mediator. In addition, the interactive content is more influential than the personalised content in building and maintaining online relationships in the B2B reseller market.